Evaluation of the Quality of Pumpkin Seed Flour and Capsules as Food Supplements - Aminuddin Syam (Faculty of Public Health, Hasanuddin University, Makassar, 2022)
Pumpkin seeds contain a variety of useful nutrients, so they become a food supplement. This study aimed to evaluate the quality of pumpkin seed flour and capsules. This study used the experimental method. The pumpkin used came from a local market in Makassar City. Cleaned pumpkin seeds-then dried in the sun for ± 7 hours. After that, put them in the oven at a temperature of 70-75°C for 3 hours. Next, blended them until they became smooth flour and sieved through a 70 mesh sieve. Put the flour into a capsule shell size 00. The quality of pumpkin seed flour and capsules is tested at the Neutraseutical Laboratory and the Integrated Laboratory of Hasanuddin University. The evaluation of flour quality was carried out with 3 indicators which are the moisture content test, the incompressible density test, and the flow time test. Meanwhile, the evaluation of capsule quality was also carried out with 3 indicators, which are the time disintegration test, the weight diversity test, and the shelf-life test. Based on the evaluation of flour quality, pumpkin seed flour meet the required standards for the moisture content test (3.57%) and the incompressible density test (0.2427 g/cm3), but did not meet the required standards for the flow time test. Furthermore, pumpkin seed capsules meet the required standards for the three indicators tested, namely, the weight diversity (according to Pharmacopeia 1 edition 3), the time disintegration (6 minutes) and the shelf-life (115 days). Pumpkin seed flour and capsules can be used as food supplements because they meet the required standards to evaluate quality.